Prescribing patterns and healthcare costs of gout. (3rd June 2019) - Lee, Yi-Yun; Kuo, Li-Na; Chen, Jin-Hua; Lin, Yi-Chun; Chen, Lung-Fang; Ko, Yu
Abstract: Objective/methods: The Longitudinal Health Insurance Database (LHID) 2010 was used to identify gout cases and their number of gout flares. Results: Out of 21, 376 gout patients, a total of 3561 (16.7%) had frequent gout flares (≥3 gout flares/year). Average all-cause healthcare utilization (35.9 visits vs. 30.7 visits; p < .001) and gout-related utilization (22.7 visits vs. 15.6 visits; p < .001) were higher in frequent gout flare patients than in those with infrequent gout flares. The median gout-related cost (USD 369 vs. 285; p < .001), but not all-cause costs ( p = .25), were higher in frequent gout flare patients compared to the infrequent group. Over 55.8% of the flares were treated with colchicine + NSAIDs. Conclusions: In conclusion, patients with frequent gout flares had higher healthcare utilization and gout-related healthcare costs. Colchicine + NSAIDs are commonly used therapy for gout flare.